Spatial strategies for organizing the rivervalley by the approach of promoting the health of citizens between the Modiriat Bridge and Hemmat Bridge - jamaleddin honarvar; mohammad ali tabarsa (تحقیقات کاربردی علوم جغرافیایی)
Many contemporary urban environments are not self-sufficient with the physical and mental characteristics of the residents. Proper and purposeful design of urban environments can reduce the risks to health. The rivers of urban valleys and their open spaces are our natural and national wealth and heritage. Their value in urban plans remains unknown. In this study, in order to organize spatial space along urban rivers with a health promotion approach to achieve suitable environmental conditions for the survival of Darkeh River in Tehran (between the Modiriat bridge and Hemmat highway) and improving the quality of the surrounding environment. The research method was descriptive-analytical with survey technique. Using SPSS and LISREL8.80 software, the descriptive data of the questionnaire were analyzed. Internal and external environmental factors have been identified through field interviews from residents of three neighborhoods of IranZamin, DehVanak and the scope of the project using SWOT method. Using the Pearson continuity test and the SEM continuity diagram, it was found that there are four direct components of river flow organization (safety, continuity, vitality, flexibility) and improving the health of citizens in these three neighborhoods. At the end of the conceptual model, based on the effect of independent variables of organizing river-valleys on the dependent variables of citizenschr('39') health, it was presented and drawn and the fit of the conceptual model was confirmed using standard values ​​of T test. In the end, based on the current situation and analyzes, 11 strategies and 39 design strategies have been presented.